2019
DOI: 10.5194/bg-16-4145-2019
|View full text |Cite
|
Sign up to set email alerts
|

Simulated wild boar bioturbation increases the stability of forest soil carbon

Abstract: Abstract. Most forest soils are characterised by a steep carbon gradient from the forest floor to the mineral soil, indicating that carbon is prevented from entry into the soil. Bioturbation can facilitate the incorporation of litter-derived carbon into the mineral soil. Wild boar are effective at mixing and grubbing in the soil and wild boar populations are increasing in many parts of the world. In a 6-year field study, we investigated the effect of simulated wild boar bioturbation on the stocks and stability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…However, relative losses in SOC were even more pronounced in the subsoil, indicating that the sampling bias might have been small. However, it should be mentioned that mass-based instead of depth-based sampling (Don et al, 2019) or at least an a posteriori soil mass correction (Ellert and Bettany, 1995) would be indispensable to accurately estimate SOC stock changes.…”
Section: Linking Losses In Soil Organic Carbon To Changes In Soil Strmentioning
confidence: 99%
“…However, relative losses in SOC were even more pronounced in the subsoil, indicating that the sampling bias might have been small. However, it should be mentioned that mass-based instead of depth-based sampling (Don et al, 2019) or at least an a posteriori soil mass correction (Ellert and Bettany, 1995) would be indispensable to accurately estimate SOC stock changes.…”
Section: Linking Losses In Soil Organic Carbon To Changes In Soil Strmentioning
confidence: 99%
“…In a controlled experiment, regular grubbing by wild boar was simulated in two forest areas in Germany in 24 plots for 6 years. Don et al (2019) found no effects of grubbing disturbance on SOC stocks, but in contrast, labile SOC from the forest floor became protected and partly stabilized in the mineral soil. Thus, wild boar grubbing actually enhanced SOC stability.…”
Section: No Threat To Global Soil Carbon Stocks By Wild Boar Grubbingmentioning
confidence: 74%
“…The impact of large animals on soil carbon stocks varies, partly due to differences between biomes and scales, herbivore assemblages and densities and soil community adaptation (Figure 1 and Tables 1 and S1) 6,[54][55][56][57] . For example, herbivores can help preserve soil carbon by maintaining permafrost in the Arctic 58 , maintaining below-ground carbon in fire-prone ecosystems 59,60 , stabilising soil carbon through soil mixing 61 and through the activities of their associated soil macrofauna (e.g. earthworms, dung beetles [62][63][64] ).…”
Section: Carbon Stocks In Persistent Reservoirsmentioning
confidence: 99%